METHODS OF CALCULATION OF OWN VALUES AND OWN VECTORS OF THE MATRIX IN EXCEL SWITCHES - Tolbatov , Yu. A. (Problems of Informatization and Management, 2005)
The paper considers three methods for calculating the eigenvalues and eigenvectors of the matrix in the shell of Excel spreadsheets (ET). The method of finding the eigenvalues of the matrix using the built-in mathematical function for calculating the determinant MOPRED and the program "Solution Search", as well as the numerical method of excluding the found eigenvalues from the characteristic equation.